The Dynamic of ASEAN Tourism Forum (ATF) in Tourism Development in ASEAN Countries - Salam, Usmar (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
ATF, or the ASEAN tourist Forum, was created in 1981 to help Southeast Asia become more cohesive in its tourist industry. Through cooperation between state and non-state actors within ASEAN, the ATF expands the list of actors that contribute to the promotion of ASEAN as a common tourism destination. Nevertheless, it is still to be determined how effectively the ATF achieves this goal, namely, whether it functions as a platform for competition rather than cooperation. The present study utilises a qualitative case study approach to examine the activities, responses, and outcomes of the ATF throughout its existence. The primary emphasis is on the dynamic interplay between cooperation and competitiveness among member states of the ATF, particularly within the framework of ATSP 1 and ATSP 2. The findings show that while the ATF has promoted regional tourism collaboration, competition among member countries sometimes limits deeper integration. The results also show that some countries prioritize domestic tourism over integrated regional destinations due to their domestic conditions. This analysis uses tourism to shed light on Southeast Asian regionalization in the ATF. Access to this information also suggests ways to create more effective, harmonious, and comprehensive policies.